Lesiones odontoclásticas reabsortivas y enfermedad periodontal en el gato : hallazgos clínicos y características ultramicroscópicas en dientes normales, patológicos y sometidos a terapia periodontal - Saccomanno, Daniela Marcela (2015)
In veterinary medicine, particularly in feline patients, oral and specifically dental\ndiseases, occupy an important place in everyday clinical-surgical practice. Among the pathologies that affect the tooth and its support apparatus, periodontal disease\n(PD) and odontoclastic resorptive lesions (LOR) are the most common.\nThere are numerous investigations using electron microscopy (SEM) that describe the characteristics of dental tissues in humans. However, there are only few\nreports on the characteristics of cement and dentin in normal feline teeth, and none\nassociated with the different regions of the tooth and the different occlusal forces\nthat they support. Regarding oral diseases, no papers were found that relate the\nPD with alterations in the architecture of the cement or pulp dentine, or that\ndescribe the presence of root resorption because of the PD, not associated with\nLOR. Therefore, the main purpose of this research was to describe the structural\ncharacteristics of dentin and cement of mature permanent teeth of cats (normal and naturally affected by LOR and PD (and their modifications with periodontal therapy) for clinical therapeutic and research purposes, particularly using SEM and\ndigital image analysis.\nThe research was supported by the CICUAL (FCV-UBA), with the consent of the\nowners of the patients included in this study, and was divided into 4 parts:\nStudy of normal and pathological dentin: 48 healthy teeth, under different occlusal forces obtained from 6 young adult cats and 6 senior adult cats were included. Different forms of dentinal tubules were observed, but the rounded-elliptical was\npredominant. The average diameter of the ducts of the radicular cervical third was\n1.0581 ± 0.2590 microns, while in the apical third was 1.0248 ± 0.2931 microns.\nFrom the results, it is concluded that the diameter, area and density decrease on the dentinal tubules in a coronal-apical sense and that its density decreases with increasing age. Regarding the dentin of teeth involved in EP, 8 affected upper\ncanines were evaluated. In all cases, the diameters and areas of the dentinal\ntubules showed values lower than those obtained from normal teeth, while the\ntubular density was higher in affected teeth. Also, the dentin of 9 teeth affected with LOR were studied, in which the diameter and area of the tubules had lower\nmeasurement values than those obtained from normal teeth. The tubular density\nwas smaller in the cervical third and higher in the apical third of affected pieces\nwith respect to normal.\nStudy of normal and pathological cement: 12 cats were used, of which 75 dental roots were obtained from 54 normal teeth that supported different (high, medium, low) occlusal forces. Through observations, it could be verified that the cement\nsurface has variations, according to the morphology and arrangement of Sharpey\nfibers, whose density decreases in a corono-apical direction. Extrinsic fibers\nmeasurements showed a diameter of 4.43 ± 1.39 microns. In all thirds, the\ndiameter of extrinsic fibers of teeth undergoing maximum occlusal forces were\nsignificantly higher than those of the other two groups. To characterize the cement affected by severe EP, 36 roots from 14 adult cats were studied, being able to establish a relationship between this condition and the presence of root resorption.\nThe cervical and middle thirds were most affected (including root bifurcation\nlesions and cementoenamel junction) and some resorptions were deep enough to engage the root dentin. They were also analyzed 20 roots of 18 teeth with LOR,\nextracted from 14 affected cats. The root resorptions were mainly observed in the\ncervical third of the root, particularly in the furcation or CEJ (in single rooted teeth).Effect of periodontal treatments on the radicular surface: 27 roots corresponding to\n20 teeth with EP (grades 3 and 4) were used. Two treatment methods were\ncompared: manual cleaning (with Gracey curette No. 11/12) and mechanical\ncleaning with ultrasonic scaler (US). Also, one group of each treatment was\npolished with rotary instruments and a rubber cup. The best results were obtained with the application of US and polishing did not affect the results significantly.\nEpidemiology of oral and dental diseases in cats: feline data of 103 patients were surveyed, completing ad-hoc spreadsheets. The most significant results were: a high prevalence of periodontal disease (91.26%) and LOR (41.8%) was confirmed,\nbeing the most affected age groups those between 10 and 14 and between 6 and\n14 years old respectively. No association between PD or LOR and systemic\ndiseases was found, although a correlation of the presence of EP and the soft dietwas. The use of radiographic method allowed the detection of 69 lesions not detected during the clinical examination, or complement and extend the information provided by it.\nIt is hoped that the data provided by this research will contribute to greater and\nbetter development of dentistry in the cat species, which is relegated in veterinary medicine in general and in dentistry in particular.